Regulation by non-coding RNAs (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
Regulatory non-protein-coding RNA genes and their transcripts were first found and characterized in bacteria but encompass all biological kingdoms. The complexity of non-coding RNAs (ncRNAs) in terms of number and types increases with degree of biological development, whereby humans and other primates appear to have the largest number. Many regulatory ncRNAs base-pair to a target RNA or DNA and inhibit target function. Bacterial ncRNA genes largely respond to environmental stress conditions and help protect the organism from adverse conditions. The prokaryotic RNAs are for the most part small (<200 bp) and are commonly referred to as small regulatory RNAs (sRNAs). Eukaryotic RNAs consist of small <200 nt RNAs and large >200 nt (termed lncRNAs). The eukaryotic small RNAs include miRNAs, siRNAs, and piRNAs. miRNAs inhibit mRNA functions and may also be associated with cancer. lncRNAs functions are multifaceted and include epigenetic regulation and animal development. The bacterial and archeal immune system CRISPR, and the eukaryotic piwi-interacting RNAs (piRNA) immune system that inhibits mobile elements in germ line cells both function by via RNA transcript/ target DNA heteroduplex base-pairing are a specific class of RNAs that protect cells from invading transposons/and or viruses. siRNAs function in plant and invertebrate immune systems and protect against viral infections. [...]